Enhancing Listening Ability with TEDx Talks - Yugi Diraga Prawiyata; Ade Miftahul Jannah; Alifah Zuhroh; Nadin Qyrana Azzahra Alvin (STKIP Taman Siswa Bima, 2025)
Listening is a crucial skill in English language learning, yet many first-semester English Education students face challenges in comprehending main ideas, understanding details, and adapting to various accents. This study aims to investigate the effectiveness of TEDx Talks as a supplementary medium to enhance students’ listening skills, engagement, and autonomous learning. A descriptive quantitative approach was employed, involving 17 students who participated in an online survey using a 14-item Likert-scale questionnaire. The questionnaire measured students’ perceptions of comprehension, vocabulary acquisition, recognition of idiomatic expressions, and confidence in listening. The results show that the majority of students responded positively to TEDx Talks, reporting improvements in understanding main ideas, expanding vocabulary, recognizing intonation patterns, and increasing motivation for independent learning. However, some students still experienced difficulties with specific details and unfamiliar accents. These findings suggest that TEDx Talks can serve as an effective supplementary resource to provide authentic, context-rich input, support receptive skill development, and foster learner autonomy. Integrating TEDx Talks into listening courses can therefore enhance both comprehension and motivation, contributing to more effective English language instruction for students at the early stages of proficiency.